2007
DOI: 10.1103/physrevb.75.205303
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-induced acoustoelectric vibrations in surface-gated GaAs-based quantum devices

Abstract: We present the results of a numerical investigation which show the excitation of acoustoelectric modes of vibration in GaAs-based heterostructures due to sharp nanosecond electric-field pulses applied across surface gates. In particular, we show that the pulses applied in quantum information processing applications are capable of exciting acoustoelectric modes of vibration including surface acoustic modes which propagate for distances greater than conventional device dimensions. We show that the pulse-induced … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The electron-phonon coupling Hamiltonian is given by Eq. 1 with Z S = σ z [8,21,22]. Z S (t) has Fourier frequencies W = ±{0, Ω , ω 0 , ω 0 ± Ω } and coefficients…”
Section: Arxiv:13060690v2 [Quant-ph] 7 Jun 2013mentioning
confidence: 99%
“…The electron-phonon coupling Hamiltonian is given by Eq. 1 with Z S = σ z [8,21,22]. Z S (t) has Fourier frequencies W = ±{0, Ω , ω 0 , ω 0 ± Ω } and coefficients…”
Section: Arxiv:13060690v2 [Quant-ph] 7 Jun 2013mentioning
confidence: 99%
“…The details of the SAW potential itself have been modeled by Rahman et al. in 3D using finite‐element methods .…”
Section: Quantized Acoustoelectric Currentmentioning
confidence: 99%
“…They found that the current quantisation should be best for a channel a little longer than the SAW wavelength. The details of the SAW potential itself have been modelled by Rahman et al in 3D using finite-element methods [26,27].…”
mentioning
confidence: 99%